Customary Law Perspective: Legal Protection of Children as Crime Victims (Study in Parigi Moutong Regency) - Nurhayati Mardin; Vivi Nur Qalbi; Harun Nyak Itam Abu; Adiguna Kharismawan (International Journal of Law, Environment, and Natural Resources, 2025)
This study aims to analyze the implementation of legal protection for child victims of violence and the juridical implications of resolving such cases through customary law mechanisms in Parigi Moutong Regency. Employing an empirical juridical method, the research incorporates a conceptual approach, a case approach, and a statute approach. Data were obtained through surveys, observations, and interviews with relevant stakeholders, and analyzed qualitatively. The findings reveal that legal protection for child victims has been implemented by relevant authorities, including law enforcement and child protection agencies. These efforts involve both formal legal proceedings and non-judicial support such as victim assistance and rehabilitation provided by the Department of Women’s Empowerment, Child Protection, Population Control, and Family Planning. However, the research also highlights the ongoing practice of resolving cases particularly those involving sexual violence through customary law. Such resolutions often contradict national legal standards and principles of children's human rights. The preference for customary mechanisms among local communities and traditional leaders reflects sociocultural norms and the perceived accessibility of informal justice systems. The study underscores the need for policy harmonization between state law and customary practices to ensure the protection and fulfillment of children's rights.